A community for students.
Here's the question you clicked on:
 0 viewing
automaticloveletter
 one year ago
The incorrect work of a student to solve an equation 2(y + 8) = 4y is shown below:
Step 1: 2(y + 8) = 4y
Step 2: 2y + 10 = 4y
Step 3: 2y = 10
Step 4: y = 5
Which of the following explains how to correct Step 2 and shows the correct value of y?
The equation should be y + 8 = 4y after division by 2; y = 4
The equation should be y + 8 = 4y after division by 2; y = 6
2 should be distributed as 2y + 16; y = 4
2 should be distributed as 2y + 16; y = 8
automaticloveletter
 one year ago
The incorrect work of a student to solve an equation 2(y + 8) = 4y is shown below: Step 1: 2(y + 8) = 4y Step 2: 2y + 10 = 4y Step 3: 2y = 10 Step 4: y = 5 Which of the following explains how to correct Step 2 and shows the correct value of y? The equation should be y + 8 = 4y after division by 2; y = 4 The equation should be y + 8 = 4y after division by 2; y = 6 2 should be distributed as 2y + 16; y = 4 2 should be distributed as 2y + 16; y = 8

This Question is Closed

automaticloveletter
 one year ago
Best ResponseYou've already chosen the best response.0@TheSmartOne @Kim21

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0Either A or B, since the person screwed up when they added 2+6 rather than multiplying 2*6 :b

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0After that all you need to do is solve for y :)

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0Step 2 SHOULD have been: 2y+12=4y

anonymous
 one year ago
Best ResponseYou've already chosen the best response.02y+12=4y then subtract 2y on both sides 12=2y and then divide by 2 on both sides 6=y

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0A. 2 should be distributed as 2y + 12; y = 6 ^this would be the correct answer...again so sorry that I was offline! If you were to double check, it 6 would work. If you ever get stuck on a problem like this, just plug in the y to see if the solution would be equal:  2(y + 6) = 4y simplifies to 12+12=24

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0thats all you have to do then since its then Step 2 :) @automaticloveletter
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.